'I AM': Indigenous consciousness for authenticity and leadership. (August 2021) - Spiller, Chellie
This article encourages a move away from the excessively inward gaze of 'to thine own self be true' and explores 'I AM' consciousness as a starting point. An I AM approach encourages a move from the measurable self to the immeasurable expansiveness and mystery of our own becoming. It is to step beyond the lines drawn around the 'true self' or the lines that others would have us draw. I AM consciousness reflects an ancient Indigenous thread that echoes through millennia and reminds humans that we are a movement through time, and each person is a present link to the past and the future, woven into a fabric of belonging.